2012
DOI: 10.1095/biolreprod.112.102608
|View full text |Cite
|
Sign up to set email alerts
|

FZD1 Regulates Cumulus Expansion Genes and Is Required for Normal Female Fertility in Mice1

Abstract: WNT4 is required for normal ovarian follicle development and female fertility in mice, but how its signal is transduced remains unknown. Fzd1 encodes a WNT receptor whose expression is markedly induced in both mural granulosa cells and cumulus cells during the preovulatory period, in a manner similar to Wnt4. To study the physiological roles of FZD1 in ovarian physiology and to determine whether it serves as receptor for WNT4, Fzd1-null mice were created by gene targeting. Whereas rare Fzd1(-/-) females were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
(53 reference statements)
1
28
0
Order By: Relevance
“…At the molecular level, we found alcam to be regulated by Fzd3 signaling. Our data strongly support earlier findings (Gessert et al, 2008;Lapointe et al, 2012;Prieve and Moon, 2003), demonstrating that alcam is a direct target gene of β-Cateninindependent Wnt signaling at the transcriptional level. Therefore, we can add alcam to the currently very short list of two direct target genes of β-Catenin-independent Wnt signaling in vertebrates: eaf2 (Maurus et al, 2005) and pcdh8 (Schambony and Wedlich, 2007).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…At the molecular level, we found alcam to be regulated by Fzd3 signaling. Our data strongly support earlier findings (Gessert et al, 2008;Lapointe et al, 2012;Prieve and Moon, 2003), demonstrating that alcam is a direct target gene of β-Cateninindependent Wnt signaling at the transcriptional level. Therefore, we can add alcam to the currently very short list of two direct target genes of β-Catenin-independent Wnt signaling in vertebrates: eaf2 (Maurus et al, 2005) and pcdh8 (Schambony and Wedlich, 2007).…”
supporting
confidence: 92%
“…However, analyses regarding a potential function of Alcam during pronephros development are not yet available. In addition, earlier experiments suggested that alcam is regulated by non-canonical Wnt signaling (Gessert et al, 2008;Lapointe et al, 2012;Prieve and Moon, 2003). It remained elusive how alcam is regulated by β-Catenin-independent Wnt signaling and whether alcam is involved in Wnt mediated aspects of nephrogenesis.…”
Section: Introductionmentioning
confidence: 97%
“…Our results indicate that the Wnt signaling pathway is vital to regulating follicular development in the ovary. So far, studies have showed that Frizzled 1 and Frizzled 2 are found in different parts of the rodent ovary (Chan et al, 1992;Wang et al, 2010b;Lapointe et al, 2012). Interestingly, in human cumulus cells, Frizzled 3 can bind to Wnt 2, but it is not known which downstream signaling pathways are activated following this interaction (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wnt signaling has been implicated in ovarian development, oogenesis, and early embryonic development (Chan et al, 1992;Vainio et al, 1999;Ricken et al, 2002;Boerboom et al, 2005;Hsieh et al, 2002Hsieh et al, , 2005Kimura et al, 2006;Wu et al, 2007;Wang et al, 2009Wang et al, , 2010bLapointe et al, 2012). Vainio et al (1999) found that Wnt 4-deficient mice exhibit sex reversal and a paucity of oocytes in the newborn ovary, while mice null for Frizzled 4 are infertile and exhibit impaired function of the corpus luteum .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation